(untitled) - Clark, John R. (Rome, 1992)
This report identifies governmental actions that can lead to effective management of coastal resources and strengthening the national capacity for effective coastal resources management through integrated coastal zone management.
Keywords: Integrated coastal zone management,Marine resources